2018
DOI: 10.1002/adhm.201701510
|View full text |Cite
|
Sign up to set email alerts
|

Conceptually Novel Black Phosphorus/Cellulose Hydrogels as Promising Photothermal Agents for Effective Cancer Therapy

Abstract: Black phosphorus (BP) has recently emerged as an intriguing photothermal agent in photothermal therapy (PTT) against cancer by virtue of its high photothermal efficiency, biocompatibility, and biodegradability. However, naked BP is intrinsically characterized by easy oxidation (or natural degradation) and sedimentation inside the tumor microenvironment, leading to a short-term therapeutic and inhomogeneous photothermal effect. Development of BP-based nanocomposites for PTT against cancer therefore remains chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 201 publications
(162 citation statements)
references
References 51 publications
0
158
0
1
Order By: Relevance
“…In particular, black phosphorene is expected to be applicable to biomedical fields owing to its good optoelectronic properties, low cytotoxicity, high photothermal conversion efficient, excellent biocompatibility, and biodegradability . Several researches have shown that black phosphorene can be used for drug delivery platforms, cancer theranostics, photodynamic, and photothermal therapy . 2D V‐V binary materials share the similar atomic structures and extranuclear electronic structures with black phosphorene, with high surface area, tunable bandgap, and fascinating optoelectronic properties, making them promising 2D biomedical materials.…”
Section: Applications Of 2d V‐v Binary Materialsmentioning
confidence: 99%
“…In particular, black phosphorene is expected to be applicable to biomedical fields owing to its good optoelectronic properties, low cytotoxicity, high photothermal conversion efficient, excellent biocompatibility, and biodegradability . Several researches have shown that black phosphorene can be used for drug delivery platforms, cancer theranostics, photodynamic, and photothermal therapy . 2D V‐V binary materials share the similar atomic structures and extranuclear electronic structures with black phosphorene, with high surface area, tunable bandgap, and fascinating optoelectronic properties, making them promising 2D biomedical materials.…”
Section: Applications Of 2d V‐v Binary Materialsmentioning
confidence: 99%
“…Both the top view of few‐layered GeP (Figure b) and the side view of monolayer GeP (Figure c) show its intrinsic anisotropy. Liquid‐phase exfoliation (LPE) therefore may be an ideal process to fabricate 2D GeP nanosheets of tunable nanometer sizes (depending on LPE conditions such as ultrasonic and centrifugal conditions) and large yield . Their preparation process is illustrated in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Xing et al fabricated a novel BP/cellulose hydrogel for PTT against cancer. Due to its excellent flexibility, improved stability, and notable photothermal response, BP/cellulose hydrogels show great potential for cancer therapy.…”
Section: Biomedical Applications Of Bpmentioning
confidence: 99%